Greenhouse Gas System Information System - Mohd Yusof, Muhammad Imran; Shahreen Kasim (Applied Information Technology And Computer Science, 2023)
Greenhouse Gas Information System is a calculating system for greenhouse gases for Sawit Kinablu Sdn Bhd.The system is developed to replace Sawit Kinabalu way’s of doing the calculation manually.Thus, the system is designed for web-based platform to manage the data from its operating unit. The targeted user of this system will be the workers from the company such as Admin which will operate the whole system, The Manager which will operate the system based on their own operating unit and the clerk whom will be doing most of the work managing the data such as collecting it and do the calculations based on the data. The system consist of 5 main modules and it is developed fully using Laravel and XAMPP as its database. The system will be able to make Sawit Kinabalu have easier time managing the data regarding greenhouse gases for the whole company.